The politics of Kavango-Zambezi (KAZA) TFCA in Botswana - Mogende, Emmanuel (Department of Environmental and Geographical Science, 2017)
Transfrontier conservation areas (TFCAs) are considered the latest evolution of a more holistic approach to transnational environmental management that brings together conservation and development agendas. As part of bio political governance, TFCAs are ecologically, economically and politically motivated. Using a discourse analytical perspective of claims advanced for TFCAs in Southern Africa, this study explores how Kavango-Zambezi (KAZA) TFCA has been motivated. The study questions the interests of Botswana government participation in the KAZA TFCA and examines the effects of the KAZA TFCA on local communities. This study employs a qualitative approach employing triangulation methods of data collection. KAZA is one of the largest and most ambitious transboundary initiative in the world that stretches across the political borders of five sovereign states. KAZA acknowledges that nature knows no boundaries hence conservation corridors should traverse political boundaries and borders of the state. Against this backdrop, the rationale for KAZA is to provide the large herds of elephants (approximately 120,000) in Botswana with access to large area of grazing land. The study demonstrates how the burgeoning elephant population is inextricably linked with border policing, tourism and conservation. KAZA considers participation and local community involvement in planning and decision making as legitimate for sustainable natural resource management. However, the current realities exist in contrast to these considerations. The study reveals that there is a disparity between theory and practice as KAZA is yet to deliver its promises to the local communities. The thesis asserts that it is critical to view KAZA as a complex, evolving and long-term initiative that will be interesting to follow in the future.